2013
DOI: 10.4236/pp.2013.46073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Meal and Genotype of CYP2C19 on the Pharmacokinetics of Proton Pump Inhibitors in Healthy Japanese Subjects

Abstract: Objectives: To evaluate the influence of meals on the pharmacokinetics of omeprazole and rabeprazole and to investigate these PPIs with reference to CYP2C19 genotypes in healthy Japanese men. Methods: This was a randomized, open label, four-way crossover study. Twelve healthy Japanese male volunteers received a single oral dose of either 20 mg omeprazole or 10 mg rabeprazole, in the fasted state and after a standardized breakfast. Results: Between the administration of omeprazole in the fasted state and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
(46 reference statements)
0
6
1
Order By: Relevance
“…Except for the delay of t max (2.2 h for (1) vs. 3.5 h for (3)), no significant changes were observed in AUC and C max values between all the investigated regimens. Shinkai et al [42] reported the nonsignificant effect of food on 20 mg omeprazole pharmacokinetic parameters (namely C max , AUC 0-t , t max , and t1 ⁄2 ); however, in this study, drug formulation was not mentioned.…”
Section: Food Effectcontrasting
confidence: 56%
See 2 more Smart Citations
“…Except for the delay of t max (2.2 h for (1) vs. 3.5 h for (3)), no significant changes were observed in AUC and C max values between all the investigated regimens. Shinkai et al [42] reported the nonsignificant effect of food on 20 mg omeprazole pharmacokinetic parameters (namely C max , AUC 0-t , t max , and t1 ⁄2 ); however, in this study, drug formulation was not mentioned.…”
Section: Food Effectcontrasting
confidence: 56%
“…To assess the effect of a meal on the pharmacokinetic parameters of rabeprazole tablets, Shinkai et al [42] performed a randomized, open-label study in 12 healthy volunteers. Each of the participants ingested a single 10 mg dose of rabeprazole either while fasting or after breakfast that contained on average 712 kcal.…”
Section: Food Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been suggested that careful judgment and monitoring are needed for administration in patients with severe liver disease [9]. Some past reports [10,11] have suggested that the pharmacokinetic effects of rabeprazole from food may not be significant. According to a past report [11], no clinically relevant differences were detected in the area under the curve for the plasma concentration-time profiles (AUC), maximum plasma concentration (C max ), and half-life (T 1/2 ) of rabeprazole between fasted and fed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…pylori status and CYP2C19 polymorphism genotyping H. pylori infection status was determined by measuring titers of anti-H. pylori IgG in the serum samples using an EIA kit (E Plate "Eiken" H. pylori-antibody II; Eiken Chemical Co. Ltd., Tokyo, Japan). A genotype of CYP2C19 gene, which encodes a hepatic enzyme involved in metabolism of esomeprazole, was determined using fluorescence correlation spectroscopy (Shinkai et al 2013). Genomic DNA was extracted from venous white blood cells, and used as a template for polymerase chain reaction (PCR) to specifically amplify fluorescent-labeled DNA fragments with wild-type (wt) or mutant sequence.…”
Section: Measurement Of Gastric Acid Secretion Capacitymentioning
confidence: 99%